Learning the Values of Multicultural Islamic Education as an Effort to Solve Santri Delinquency - Renaningtyas, Peni Catur; Ramlan, Siti Rosilawati; Ghony, Djunaidi (IJIBS, 2023)
Pesantren is an Islamic educational institution that has multicultural characteristics. The students who study at Islamic boarding schools generally come from various regions in Indonesia and even other countries with various ethnicities, races, cultures, languages, and family backgrounds from different socio-economic backgrounds. There are also variants of the education system in pesantren ranging from formal, non-formal, and informal education. The variety of diversity handled by an Islamic boardischoolsool often causes various phenomena of friction between students. So that a formula or approach to solving students' misbehavior is needed in solving and building constructive solutions through understanding, attitudes, and behavior of mutual respect in instilling the values ​​of multicultural Islamic education that have been developed in Islamic boarding schools. This study aims to analyze and find the basis of values, learning processes, and educational models of Islamic boarding schools in multicultural Islamic religious learning as a conflict resolution for students at Islamic boarding schools Nurul Islam Antirogo and Islamic boarding schools al-Qodiri Jember. This study uses a qualitative approach, a type of case study with a multi-site design. Data collection uses in-depth interviews, participant observation, and document studies. Data analysis used interactive analysis the Miles & Hubermantechnique of checking the validity of the data is used by credibility by using triangulation of data and sources, dependability, conformability, and transformability. The results of the research show (1) the foundation of values ​​(a) The introduction of ma'had and ta'aruf to respect each other, accept and strengthen equality not difference with the cultural values ​​of multicultural Indonesian citizenship with the core of civic virtue (ukhuwah Islamiyah, wathoniyah and basyariyah) (b) Islam rahmatan lil alamin as a religion of love, safety and peace, (c) the values ​​of aswajaan tawassuth (moderate), tawazun (balanced ), tasamuh (tolerance), ta'awun (help), husnudlan (favorable) and i'tidal (fair) in the process of multicultural Islamic religious education and solving students' problems/conflicts. The cause of the santri conflict is the difficulty factor in building new relationships with differences. The conflict resolution approach develops from Levin: parsing problems, solving problems, removing or eliminating problems, building reconciliation, and developing togetherness.